Dual Effects of Alpha-Arbutin on Monophenolase and Diphenolase Activities of Mushroom Tyrosinase - Qin, Liang; Wu, Yang; Liu, Youting; Chen, Yiming; Zhang, Peng (PLOS ONE, 2014)
The effects of α-arbutin on the monophenolase and diphenolase activities of mushroom tyrosinase were investigated. The results showed that α-arbutin inhibited monophenolase activity but it activated diphenolase activity. For monophenolase activity, IC50 value was 4.5 mmol·L−1 and 4.18 mmol·L−1 of α-arbutin could extend the lag time from 40.5 s to 167.3 s. Alpha- arbutin is proposed to be regarded as a triphenolic substrate by the enzyme during catalyzation, leading to the suicide inactivation of the active site of tyrosinase. For diphenolase activity, α-arbutin acted as an activator and its activation mechanism was mixed type activation. To reveal such activation, it should be mainly refered to the conformational changes in tyrosinase caused by the interaction of α-arbutin with residues located at the entrance to the active site, and the decrease of the effect of suicide inactivation.